La descripción de los lindes: estudio de los verbos usados en los diplomas asturleoneses (s. VIII-1230) - Pérez Rodríguez, Estrella; Pérez Rodríguez, Estrella (Turnhout: Brepols, 2018)
Los lindes desempeñan un papel muy importante en los diplomas notariales de la Edad Media y suelen aparecer en ellos en dos contextos diferentes: la descripción de la propiedad y tres tipos de fórmulas (las que introducen tales descripciones, las que las cierran o las que resumen el acto jurídico del diploma). Ese es el ámbito de análisis del presente trabajo dentro del corpus textual formado por las ca. 10.000 cartas redactadas en el reino de Asturias y León (excepto la Gallaecia) entre el s. VIII y 1230. Su objetivo es identificar los verbos empleados en tal contexto y estudiar el uso de cada uno. Para ello los 124 verbos localizados han sido divididos en 15 grupos de acuerdo con su significado y, antes del estudio de cada grupo, se ha incluido una tabla con la información numérica más relevante de cada verbo: número de ocurrencias, entidades que constituyen su primer argumento, construcción, voz y preposiciones que lo acompañan. El trabajo muestra, entre otras diversas particularidades, que 23 de esos verbos (abincipio, adlimito, aflingo, asopear, contermino, conuerto, destremo, distermino, extremo, fingo, fligo, giro, inuergo, inuerto, iscingo, perambulo, preanfingo, protendo, reafigo, reafingo, reafligo, recudo y redescendo) se usan exclusivamente en el ámbito de la delimitación de los lindes y otros 12 (adfigo, adfligo, affronto, delimito, determino, distinguo, figo, includo, refigo, refingo, refrigo y termino) se emplean mayoritariamente en él. En términos absolutos el verbo más usado es discurro (más de 1.100 veces), pero referido casi siempre a caminos; le siguen determino (más de 700 veces), uado y adf(l)i(n)go (más de 550), y iaceo y termino (más de 300). Los grupos verbales más ricos son los de trayectoria, con 55 verbos, y los de contacto y delimitación con 14 y 12, respectivamente. Por otro lado, dentro de este ámbito léxico se observa la continuidad e innovación característica de la lengua de los diplomas medievales asturleoneses, pues entre estos verbos los hay de origen antiguo, pero también neologismos, tanto tardoantiguos (contermino, delimito, departio, giro, talio) como medievales, y estos últimos pueden ser léxicos (abincipio, adlimito, adtermino, affronto, extremo, iuncto, preanfingo, recudo, redescendo, reaf(l)i(n)go, retorno, y los localismos destremo e iscingo) o semánticos (ferio, leuo, lexo, pleco y el localismo extermino). Igualmente se puede observar la habitual interferencia del romance en verbos como aplanar, asopear, atrauessar, derribar, filio, passar, salir, tomar; los dos primeros exclusivos de la zona asturiana.
Property boundary lines play quite an important part in medieval charters and usually appear in them in two different contexts: on the one hand, in the description of the property, which can be done by individual sides, in a continuous and circular manner, or in a combination of both, along with some other briefer forms; on the other hand, in the formulae, which are of three kinds: those introducing descriptions, those finishing them and those summarizing the legal act. This is the scope of our analysis, whose textual sources are c. 10,000 Latin charters written in the kingdom of Asturias and Leon (except in Gallaecia) between the eighth century and 1230. Our aim is to identify the verbs used and to examine how they are used. To this end, we have classi6ed the 124 located verbs into 15 groups according to their meaning. Before the study of each group, we have included a table with the most relevant numerical information concerning the verbs: number of cases, entities that are their 6rst argument, construction, voice and prepositions introducing the prepositional syntagm that accompanies them. 23 of these verbs are exclusively used in the scope of boundary delimitation: abincipio, adlimito, aflingo, asopear, contermino, conuerto, destremo, distermino, extremo, fingo, fligo, giro, inuergo, inuerto, iscingo, perambulo, preanfingo, protendo, reafigo, reafingo, reafligo, recudo and redescendo; while another 12 verbs are mostly found in this context: adfigo, adfligo, affronto, delimito, determino, distinguo, figo, includo, refigo, refingo, refrigo and termino. In absolute terms, the most frequent verb is discurro (more than 1100 times), almost always related to roads; determino appears more than 700 times, uado and adf(l)i(n)go more than 550; iaceo and termino over 300. The richest verbal groups are those of motion, with 55 verbs, and of attachment and demarcation, with 14 and 12, respectively. The majority of these verbs are mainly used in the descriptions of boundaries and many exclusively so, as is the case of the verbs meaning to lead, to conduct, and those concerning acquisition, contact, motion (except circumdo, extendo and protendo) and attachment (except coniungo). In the formulaic contexts, the demarcation verbs adlimito, delimito, determino and termino prevail, together with circumdo, concludo, decido, distinguo, includo and iscingo. The boundary line is the first argument of the verbs of contact (in 773 occurrences, 43.2% of the total), motion (in 753 occurrences, 42.1%) and, far behind these, inclusion (168 occurrences, 9.4%). lnstead, the described property is usually accompanied by verbs of separation (86, occurrences) and location (82 occurrences). The demarcation elements, especially rivers and roads, are mainly the subject of motion verbs (1757 occurrences). As usually happens in the Latin of medieval charters, continuity and innovation are to be observed in the use of these verbs, since, among them, there are Latin verbs of ancient origin, but also neologisms from both the Late Antiquity (contermino, delimito, departio, giro, talio) and the Middle Ages; the latter can be lexical neologisms (abincipio, adlimito, adtermino, affronto, extremo, iuncto, preanfingo, recudo, redescendo, reaf(l)i(n)go, retorno, and the localisms destremo and iscingo ), as well as semantic ones (ferio, leuo, lexo, pleco, and the localism extermino). The interference of Romance can also be observed in verbs such as aplanar, asopear, atrauessar, derribar, filio, passar, salir, tomar; the first two exclusively from the Romance of Asturias.
Keywords: Lengua latina medieval y moderna; Lexicografía; Diplomática